2008
DOI: 10.2459/jcm.0b013e3281053abd
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Doppler echocardiography for the assessment of left atrial appendage size and blood flow velocity. A multicentre study

Abstract: Reliable LAA size and blood flow velocities can be obtained by TTE in consecutive, unselected patients. TTE identifies patients with low and high blood flow velocities in the LAA, providing helpful information for the definition of individual embolic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 22 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…However, some limitations remain in measuring the flow velocity using a transthoracic approach. Detection rate of measurable flow velocities ranged from 62% to 88% for various heart diseases with sinus rhythm or atrial fibrillation 6,7 . On the other hand, the intravenous contrast injection allows better visualization of the LAA and assessment of blood flow velocities 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some limitations remain in measuring the flow velocity using a transthoracic approach. Detection rate of measurable flow velocities ranged from 62% to 88% for various heart diseases with sinus rhythm or atrial fibrillation 6,7 . On the other hand, the intravenous contrast injection allows better visualization of the LAA and assessment of blood flow velocities 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of the transesophageal probe is semi‐invasive; hence, we hesitate to examine healthy subjects using TEE. Recent development in transthoracic echocardiography (TTE) has facilitated evaluation of the transverse size of the orifice and determination of flow velocities in the LAA, and in some reports, the efficacy of this method has been reported 6,7 . Recently, Uretsky et al demonstrated that transthoracic tissue Doppler echocardiography (TDE) could provide noninvasive physiological analysis of LAA function, and that LAA wall velocity decreased in patients with atrial fibrillation 8 .…”
mentioning
confidence: 99%
“…Pulsed Doppler sample was taken at 1 cm into the LAA orifice . To achieve optimal alignment of Doppler beam with LAA flow, the sonographer gradually modified the view by moving upward and downward in the intercostal spaces and adjusting the angle of the probe, as described in previous studies . Offline measurements of LAA E and F velocities were obtained by a trained echocardiologist blinded to TEE and clinical findings.…”
Section: Methodsmentioning
confidence: 99%
“…Receiver operating characteristic (ROC) curve analysis was then used to determine the optimal cutoff values of TTE LAA E that predicts (1) the presence of thrombus or SEC on TEE and (2) the presence of LAA dysfunction (TEE LAA E ≤ 20 cm/s). As previous studies have found that patients with AF had lower LAA flow velocities, subgroup analysis of patients with AF was also performed …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation